ANALISIS DAYA DUKUNG PONDASI SPUN PILE BERDASARKAN HASIL SPT DAN HASIL KALENDERING PADA PEMBANGUNAN JALAN TOL KATARAJA ZONE 1 - Siagian, Bermando Mangatur; Irvan Tri Nugroho (Fakultas Teknik Universitas Krisnadwipayana, 2023)
The construction of the Kataraja toll road is one of the government programs that are currently being implemented to balance the movement of people by driving. The purpose of this study is to analyze and compare the results of the calculation of the bearing capacity and settlement of the foundation. The foundation is the lowest part of the building structure which has the role of transferring the building load to the underlying soil or rock. The depth of the hard soil that becomes the foundation reaches 30 meters, so use a spun pile foundation. Analysis of pile bearing capacity and settlement needs to be considered to obtain an appropriate foundation plan and meet the requirements. There are several calculation methods in analyzing the bearing capacity and settlement of the foundation, but it is necessary to consider which method is relevant. The method used in the analysis of the bearing capacity of the pile foundation based on the SPT results is Mayerhof, the results obtained are (Qu) 633.92 kN and the calendering results using the Hilley method are (R) 1654.415 kN. Calculation of the efficiency of the pile group using the Coverese-Labbare Formula method, the result is (Eg) 0.574. Analysis of calculating the settlement of a single pile manually using the Vesic method obtained a result of (S) 2.62 cm with a reduction in permits of (Sir) 6 cm so that the single pile settlement requirements are met (SAFE). Analysis of group pile settlement manually with the Vesic method obtained results of (Sg) 5.34 cm and with the Plaxis 3D Application it was 6.71 cm with a decrease in permits referring to (BSN SNI 8460, 2017) of <15 cm, so the requirements on group pile settlement are met (SAFE).